How consistent are lordosis, range of movement and lumbo-pelvic rhythm in people with and without back pain?. Issue 1 (December 2016) - Laird, Robert; Kent, Peter; Keating, Jennifer
Abstract Background Comparing movements/postures in people with and without lower back pain (LBP) may assist identifying LBP-specific dysfunction and its relationship to pain or activity limitation. This study compared the consistency in lumbo-pelvic posture and movement (range and pattern) in people with and without chronic LBP (>12 week's duration). Methods Wireless, wearable, inertial measurement units measured lumbar lordosis angle, range of movement (ROM) and lumbo-pelvic rhythm in adults (n  = 63). Measurements were taken on three separate occasions: two tests on the same day with different raters and a third (intra-rater) test one to two weeks later. Participants performed five repetitions of tested postures or movements. Test data were captured automatically. Minimal detectable change scores (MDC90 ) provided estimates of between-test consistency. Results There was no significant difference between participants with and without LBP for lordosis angle. There were significant differences for pelvic flexion ROM (LBP 60.8°, NoLBP 54.8°, F(1, 63) = 4.31, p  = 0.04), lumbar right lateral flexion ROM (LBP 22.2°, NoLBP 24.6° F(1, 63) = 4.48, p  = .04), trunk right lateral flexion ROM (LBP 28.4°, NoLBP 31.7°, F(1, 63) = 5.9, p  = .02) and lumbar contribution to lumbo-pelvic rhythm in the LBP group (LBP 45.8 %, F(1, 63) = 4.20, NoLBP 51.3 %p  = .044). MDC90 estimates for intra and inter-rater comparisons were 10°–15° for lumbar lordosis, and 5°–15° for most ROM. For lumbo-pelvic rhythm, we found 8–15 % variation in lumbar contribution to flexion and lateral flexion and 36–56 % variation in extension. Good to excellent agreement (reliability) was seen between raters (meanr  = .88, ICC (2, 2)). Conclusion Comparisons of ROM between people with and without LBP showed few differences between groups, with reduced relative lumbar contribution to trunk flexion. There was no difference between groups for lordosis. Wide, within-group differences were seen for both groups for ROM and lordosis. Due to variability between test occasions, changes would need to exceed 10°–15° for lumbar lordosis, 5°–15° for ROM components, and 8–15 % of lumbar contribution to lumbo-pelvic rhythm, to have 90 % confidence that movements had actually changed. Lordosis, range of movement and lumbo-pelvic rhythm typically demonstrate variability between same-day and different-day tests. This variability needs to be considered when interpreting posture and movement changes.